Bombesin receptor subtype 3 as a potential target for obesity and diabetes. (September 2015) - González, Nieves; Moreno, Paola; Jensen, Robert T
<x xml:space="preserve">Abstract</x> Introduction: Diabetes mellitus and obesity are important health issues; increasing in prevalence, both in the USA and globally. There are only limited pharmacological treatments, and although bariatric surgery is effective, new effective pharmacologic treatments would be of great value. This review covers one area of increasing interest that could yield new novel treatments of obesity/diabetes mellitus. It involves recognition of the central role the G-protein-coupled receptor, bombesin receptor subtype 3 (BRS-3) plays in energy/glucose metabolism. Areas covered: Since the initial observation that BRS-3 knockout mice develop obesity, hypertension, impaired glucose metabolism and hyperphagia, there have been numerous studies of the mechanisms involved and the development of selective BRS-3 agonists/antagonists, which have marked effects on body weight, feeding and glucose/insulin homeostasis. In this review, each of these areas is briefly reviewed. Expert opinion: BRS-3 plays an important role in glucose/energy homeostasis. The development of potent, selective BRS-3 agonists demonstrates promise as a novel approach to treat obesity/diabetic states. One important question that needs to be addressed is whether BRS-3 agonists need to be centrally acting. This is particularly important in light of recent animal and human studies that report transient cardiovascular side effects with centrally acting oral BRS agonists.